2010
DOI: 10.4049/jimmunol.0903013
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Priming of CD8 T Cell Immunity to Herpes Simplex Virus Type 1 Requires Cognate TLR3 Expression InVivo

Abstract: Despite its potential for involvement in viral immunity, little evidence links TLR3 to adaptive antiviral responses. Here we show that TLR3 is required for the generation of CD8 T cell immunity to HSV-1. The magnitude of the gB-specific CD8 T cell response after flank infection by HSV-1 was significantly reduced in mice lacking TIR domain-containing adaptor-inducing IFN-β or TLR3, but not MyD88. Impaired CTL induction was evident in chimeric mice lacking TLR3 in bone marrow (BM)-derived cells. Among the dendri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 25 publications
4
77
0
Order By: Relevance
“…Others have also examined a requirement for coupling of antigen delivery to and TLR signaling in DCs in the generation of CD8 + T cell immunity through cross-presentation. Coactivation of DCs presenting protein or viral antigens with TLR3 or TLR4 ligands improved cross-presentation in vitro and in vivo (14,(76)(77)(78). By contrast, CD8 + T cell responses can be generated in vivo in the absence of TLR3 after immunization with protein antigens and poly (I:C) (79,80).…”
Section: Discussionmentioning
confidence: 99%
“…Others have also examined a requirement for coupling of antigen delivery to and TLR signaling in DCs in the generation of CD8 + T cell immunity through cross-presentation. Coactivation of DCs presenting protein or viral antigens with TLR3 or TLR4 ligands improved cross-presentation in vitro and in vivo (14,(76)(77)(78). By contrast, CD8 + T cell responses can be generated in vivo in the absence of TLR3 after immunization with protein antigens and poly (I:C) (79,80).…”
Section: Discussionmentioning
confidence: 99%
“…TLR3 has been reported to have impact on both innate and adaptive immune responses during virus infections in the periphery and CNS (13,20,21,28,29). To look into the innate response to HSV-2 infection, we isolated medulla spinalis from mice infected with HSV-2 for 6 days and examined expression of IFNs, IFN-stimulated genes, and inflammatory genes.…”
Section: Mice Deficient In Tlr3 or The Type I Ifn System Are Hypersusmentioning
confidence: 99%
“…33 Finally, cross-priming of antiviral CD8 + T cell immunity to HSV-1 requires cognate TLR3 expression in vivo, possibly on the CD8α + CD103 + langerin + dermal DC subset capable of migrating from the infected site to the draining lymph node. 31,54 Consistently, Casanova et al reported that a dominant mutation in the tlr3 gene increases susceptibility of infants to HSV-1 induced encephalitis. 55 Moreover, DC-mediated NK cell triggering was shown to be important in the absence of CD4 + T helper cells to mount a protective anti-HSV response by CD8 + T cells.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 86%
“…1). Based on the key role of Toll-like receptors (TLR) in the control of infections 30 and that of TLR2, 3 and 9 in controlling Herpes viridae-related insults, [31][32][33][34] we investigated the capacity of peripheral blood mononuclear cells (PBMC) to respond to synthetic TLR ligands such as the TLR3 ligand poly (I:C), by releasing IFNγ, as shown in healthy volunteers ( Fig. 2A).…”
Section: Abstract: Tlr Dendritic Cells Cancer Herpes Cdk Inhibitorsmentioning
confidence: 99%